Physical One‐Way Functions for Decentralized Consensus Via Proof of Physical Work - Marvin Winkler; Catharina Peither; Simon Petrick; Lothar Seidemann; Holger Jelich; Frank Kleine Jäger; Jörn Müller‐Quade; Alexander Colsmann; Hermann Nirschl; Frank Rhein (Advanced Science)
Abstract Decentralized consensus on the state of the Bitcoin blockchain is ensured by proof of work. It relies on digital one‐way functions and is associated with an enormous environmental impact. This paper conceptualizes a physical one‐way function that aims to transform a digital, electricity‐consuming consensus mechanism into a physical process. Boundary conditions for the security requirements are established and discussed as well as experimentally investigated for a specific setup based on printing and optical analysis of pigment‐carrier composites. In the context of the applied methods, this setup promises to be mathematically unclonable, steady, reproducible, collision resistant and non‐invertible and illustrates the feasibility of a physical one‐way function. Based on this, a framework for proof of physical work is conceptualized, which has the potential of a drastically lower CO2 footprint. This work initiates a progressive, interdisciplinary field of research and demands further investigations with regards to alternative setups, security definitions and strategies for challenging them.